Vaccine-associated paralytic poliomyelitis in Russian Federation during the period of changes in vaccination schedule (2006-2013 y.y.) - O. E. Ivanova; T. P. Eremeeva; N. S. Morozova; A. K. Shakaryan; A. P. Gmyl; M. L. Yakovenko; E. A. Korotkova; O. P. Chernjavskaja; O. Yu. Baykova; O. V. Silenova; A. Yu. Krasota; L. I. Krasnoproshina; et al. (Вопросы вирусологии, 2016)
The results of virologic testing of clinical materials and epidemiological analysis of vaccine-associated paralytic poliomyelitis (VAPP) cases obtained in 2006-2013 during AFP surveillance are presented. Among the 2976 cases of AFP 30 cases were vapp. 15 cases were observed in OPV recipients, whereas 15 cases were observed in non-vaccinated contacts. The age of the patients varied from 4 months to 5.5 years (13.6 ± 12.4 months old). Children younger than 1 year constituted 63.3% of the group; boys were dominant (73.3%); 53.3% of children were vaccinated with OPV; the time period between receipt of OPV and onset of palsy was from 2 to 32 days (18.7 ± 8.2). Lower paraparesis was documented in 48.3% of patients; lower monoparesis, in 37.9%; upper monoparesis, in 6.9%; tetraparesis with bulbar syndrome, in 6%. the majority of the patients (85.7%) had an unfavorable premorbid status. The violations of the humoral immunity were found in 73.9% cases: CVID (52.9%), hypogammaglobulinemia (41.2%), selective IgA deficiency (5.9%). In 70.6% cases damage to humoral immunity was combined with poor premorbid status. The most frequently observed (76%, p 0.05) represented the single type of poliovirus – type 2 (44%) and type 3 (32%). All strains were of the vaccine origin, the divergence from the homotypic Sabin strains fell within the region of the gene encoding VP1 protein, which did not exceed 0.5% of nucleotide substitutions except vaccine derived poliovirus type 2 – multiple recombinant (type 2 / type 3 / type 2 / type 1) with the degree of the divergence of 1.44% isolated from 6-month old unvaccinated child (RUS-08063034001). The frequency of the VAPP cases was a total of 1 case per 3.4 million doses of distributed OPV in 2006-2013; 2.2 cases per 1 million of newborns were observed. This frequency decreased after the introduction of the sequential scheme of vaccination (ipv, Opv) in 2008-2013 as compared with the period of exclusive use of OPV in 2006-2007: 1 case per 4.9 million doses, 1.4 cases per 1 million newborns and 1 case per 1.9 million doses, 4.9 cases per 1 million newborns, respectively.